Association of admission blood glucose and postoperation fast blood glucose with futile recanalization in patients with endovascular therapy - Dandan Chen; Yunqing Chen; Linghong Guo; Zubing Xu; Xian Liu; Xilin Xiong; Hudie Zhang; Yan Gong; Qiulong Yu; Chenying Zeng; Lanjiao Zhang; Qin Huang; et al. (BMC Neurology)
Abstract Background Futile recanalization (FR), defined as patients with long-term functional dependence despite successful recanalization, is common in patients with large-vessel stroke undergoing endovascular treatment (EVT). The present study aimed to identify the relationship between blood glucose and FR. Methods Patients admitted to our stroke center in China between November 2019 and September 2022 were recruited according to the inclusion criteria and exclusion criteria. Demographic characteristics, clinical information, laboratory data, and imaging features were collected. Patients with versus without admission hyperglycemia and with versus without postoperation hyperglycemia were compared. Results We included 378 patients (255 [67.5%] men, median age = 66.51 years); 149 (39.4%) patients had admission hyperglycemia, and 162 (42.9%) patients had postoperation hyperglycemia. Patients with versus without admission hyperglycemia more frequently suffered from FR (66.4% vs. 53.7%, P = 0.014). Meanwhile, FR was more frequently observed in patients with postoperation hyperglycemia compared to patients without (68.5% vs. 51.4%, P = 0.001). Multivariate logistic regression analysis showed that postoperation hyperglycemia but not admission hyperglycemia remained a significant correlation with FR (OR = 1.676, 95% CI 1.028–2.732, P = 0.038). Conclusion Postoperation hyperglycemia more than admission hyperglycemia was independently associated with FR in patients with EVT. Control of postoperative hyperglycemia may have a positive impact on prognosis in patients with successful recanalization.